Correction: Preparation of hexagonal GeO2 particles with particle size and crystallinity controlled by peptides, silk and silk-peptide chimeras. Issue 5 (18th December 2014) - Boix, Estefania; Puddu, Valeria; Perry, Carole C.
Abstract : Correction for 'Preparation of hexagonal GeO2 particles with particle size and crystallinity controlled by peptides, silk and silk-peptide chimeras' by Estefania Boix et al., Dalton Trans., 2014, 43, 16902–16910.